Antibacterial Effects Of Graphene In Endodontics: A Systematic Review - M C, Noushad; Vincent, Annmary; R Murali, Suchithra; Maheesan, Kavya; Rakhi R, Rakhi R; Kumar S, Nagesh (Journal of Neonatal Surgery, 2025)
This systematic review critically evaluates the antibacterial properties of graphene-based materials in endodontics, emphasizing their potential to improve root canal disinfection. Graphene, a two-dimensional carbon allotrope, is noted for its exceptional surface area, electrical conductivity, and mechanical strength, making it a promising candidate for antibacterial applications. The review explores the use of graphene, particularly graphene oxide (GO), in various endodontic contexts, including root canal sealers, irrigation solutions, and intracanal medicaments. The antibacterial mechanisms of graphene involve physical disruption of bacterial membranes, induction of oxidative stress, and inhibition of biofilm formation. A comprehensive literature search was conducted across multiple electronic databases, including COCHRANE LIBRARY, EMBASE, and MEDLINE, covering publications from 2003 to 2023. The search identified 2570 articles, which were screened for relevance. After removing duplicates and non-eligible studies, 10 articles met the inclusion criteria and were included in the review. The selection process focused on experimental studies that directly examined the antibacterial effects of graphene in endodontics, while excluding review articles, commentaries, and studies with insufficient methodological detail. The review highlights the enhanced antibacterial efficacy of graphene-based materials, particularly when combined with other antimicrobial agents like TiO2 and silver nanoparticles. It also points out the versatility of graphene in various forms and applications within endodontics. However, the review notes the need for more standardized methodologies, in vivo studies, and clinical trials to fully validate the safety and effectiveness of graphene in endodontic practice. The findings suggest that graphene holds significant promise for improving endodontic treatment outcomes.